Elevated-temperature-induced acceleration of PACT clearing process of mouse brain tissue - Yu, Tingting (Sci Rep, 2017)
Tissue optical clearing technique shows a great potential for neural imaging with high resolution, especially for connectomics in brain. The passive clarity technique (PACT) is a relative simple clearing method based on incubation, which has a great advantage on tissue transparency, fluorescence preservation and immunostaining compatibility for imaging tissue blocks. However, this method suffers from long processing time. Previous studies indicated that increasing temperature can speed up the clearing. In this work, we aim to systematacially and quantitatively study this influence based on PACT with graded increase of temperatures. We investigated the process of optical clearing of brain tissue block at different temperatures, and found that elevated temperature could accelerate the clearing process and also had influence on the fluorescence intensity. By balancing the advantages with drawbacks, we conclude that 42–47 °C is an alternative temperature range for PACT, which can not only produce faster clearing process, but also retain the original advantages of PACT by preserving endogenous fluorescence well, achieving fine morphology maintenance and immunostaining compatibility.